Physicochemical Assessment of Dairy Effluent Characteristics and Sustainable Waste Management Strategies - Shivani Singh; Jyoti Singh; Kumari Satya; Richa Srivastava; Rajeev Pratap Singh (Environmental Research and Planetary Health, 2026)
The dairy sector, a fundamental component of the global food ecosystem, has witnessed notable expansion due to technological innovations and shifting consumer preferences. Nonetheless, the management of dairy waste poses a significant challenge, with inadequate treatment resulting in severe environmental repercussions, including aquatic pollution, eutrophication, and ecological deterioration. This research examines the physicochemical characteristics of effluents from two dairies in Varanasi—Parag Industrial Dairy and Ganga Local Dairy. Parameters such as pH, dissolved oxygen, biological oxygen demand (BOD), chemical oxygen demand (COD), hardness, and nutrient concentrations were evaluated using standardized methodologies. The results indicated substantial deviations from prescribed standards, particularly for ammoniacal nitrogen, COD, BOD, as well as oil and grease concentrations, highlighting deficiencies in existing treatment protocols. The findings accentuate the necessity for enhanced effluent management strategies to ensure compliance with environmental regulations and promote sustainability. Additionally, this research underscores the potential applicability of treated effluent for agricultural use, warranting further investigation into optimal dilution ratios and microbial interactions to maintain ecological equilibrium and sustained productivity.